Assessment Of The Thickness Of The Skin-Fat Layer In Schoolchildren Of Different Age Groups - Musheghyan, Gohar; Harutunyan, Heghine; Grigoryan, Stepan; Grigoryan, Mariya; Isajanian, Mariana; Arajyan, Gohar
The rise in overweight and obesity among school-age children is currently one of the most serious public health problems. With the progress of science and medicine, obesity and the development of various problems caused by it are widespread among schoolchildren and adults in general. In this sense, as a serious problem of medical science, it is alarming and relevant (Calonje Eduardo et. al, 2020). Obesity, as one of the diseases of civilization, is the result of hypodynamia, a disturbance of fat metabolism in the body, which leads to excess weight gain. ("Obesity and overweight Fact sheet N°311".WHO. January 2015. Retrieved 2 February 2016). In this sense, it is important to take into account the age period, and the deviations observed during normal development because each age period has its characteristics of fat metabolism. It has been shown that female schoolchildren of middle school age have a higher rate of obesity, which is not only determined by gender but also by age and body composition or somatotype. Middle and high-school-aged female schoolchildren have a peripheral type of obesity, that is, fat is predominantly stored in the subcutaneous tissue of the thighs, abdomen, and buttocks. It has been shown that there is a clear correlation between fat metabolism and somatotype in middle and high school children. The results of the study suggest that physical activity should be part of a comprehensive weight loss therapy program and weight control strategy since it promotes excess weight loss and its sustainable maintenance, for which it is important to regularly monitor indicators of subcutaneous fat thickness and the relative content of adipose tissue throughout the body․
Keywords: schoolchildren; obesity